Epidemiological characteristics of cancers in patients with end-stage kidney disease: a Korean nationwide study - Min-Jeong Lee (Nature Portfolio, 2021)
Abstract Patients with end-stage kidney disease (ESKD) have been reported to have an increased risk of cancer. However, the epidemiological characteristics of cancer in ESKD patients remain unclear. Therefore, this study aimed to investigate the epidemiological characteristics of cancer in ESKD patients and the differences based on the renal replacement therapy provided. Data on ESKD patients were obtained from the South Korean nationwide cohort Health Insurance Review and Assessment Service database. This study included 58,831 eligible patients of the total 813,907 patients diagnosed with ESKD between January 1, 2007 and December 31, 2017. Of the 58,831 ESKD patients, 3292 (5.6%) were newly diagnosed with cancer. The average duration between the diagnosis of ESKD and cancer was 3.3 ± 1.9 years (mean ± standard deviation), with no differences between hemodialysis, peritoneal dialysis, and kidney transplant groups. The most commonly observed cancer sites in ESKD patients were the colorectum, lung, and liver. The incidence of cancer increased progressively among patients undergoing kidney transplant, peritoneal dialysis, and hemodialysis in that order. Hemodialysis patients were found to have an increased risk of digestive tract cancer compared with kidney transplant patients (adjusted hazard ratio = 1.9; 95% confidence interval: 1.31–2.81; P < 0.001). The study findings may be a useful reference for cancer-screening guidelines.